Pros and Cons of Professional Zakat - Nafis, Abdul Wadud; Rokhim, Abdul (LPPM, Universitas Islam Syarifuddin Lumajang, 2023)
Zakat is a mandatory form of charity given to certain groups at predefined times. According to studies, scholars differ in their opinions regarding the law on assets obtained from salary or profession. The Jumhur ulama' (most contemporary fiqh scholars) stated that zakat is required for assets obtained from the profession and employees. However, others stated that assets obtained from profession and salary are not obligatory to pay zakat. There is also disagreement regarding the nisab of assets obtained from profession and salary. Some stated that the nisab for assets obtained from an employee profession and salary is the same as the nisab for zuru' (crops), namely 5 ausuk or 653 kg of rice or wheat. Meanwhile, others stated that nisab for professional and employee salaries are the same for gold and silver, namely 20 mitsqal dinars (gold) or 200 dirhams (silver).